PERANAN MODAL DALAM PENGEMBANGAN PERTANIAN - Wahab Wahab (CV. Adiba Aisha Amira, 2024)
The role of capital in agriculture is one of the most important production factors after land in agricultural production in term of its contribusion to production velue. This study aims to determine the important role of capital in agriculture development, sources of capital for agriculturalactivities, and the roleand function of cooperatives as economic institutions in rural areas. The method used in this research is descriptive qualitative method. This type of approach is in the from of a study of scientific books and journals from works of research and thoughts produced by researchers and practitioners. Sources of data loaded come from books, journals and articles published on the website. The development of downstream agroindustry must become the concem of corporations as parf of value creation that is able to improve the welfare of stackeholders on an ongoing basis